Simulation and projection of climatic changes in the Indus River Basin, using the regional climate model COSMO‐CLM. (11th August 2016) - Huang, Jinlong; Wang, Yanjun; Fischer, Thomas; Su, Buda; Li, Xiucang; Jiang, Tong
ABSTRACT: In this article, the analysis of simulated and projected climatic changes in the Indus River Basin (IRB) is presented. The performance of the regional climate model COSMO‐CLM (CCLM) driven by the global circulation model MPI‐ESM‐LR is evaluated on the ability of reproducing temperature, precipitation, and wind pattern for the period 1961–2005. There exist quantitative biases, especially in precipitation pattern, which are associated to the diverse reproduction of the atmospheric circulation by the global circulation model. The overall results show that CCLM is able to satisfyingly capture the dominant spatial characteristics in annual temperature and precipitation time series, including the warming trend, and the seasonal variations. The changes in precipitation and temperature over the IRB are projected for the mid‐ (2046–2065) and late‐21st century (2081–2100). Relative to the baseline period (1986–2005), the average annual temperature will increase during the mid‐ and late‐21st century over the whole basin. Extreme temperature events, i.e. heat waves, are more likely to occur. An increase in summer temperature is also projected especially in the upper IRB, where the persistent increase is likely to cause further melting of glaciers. The annual precipitation will decrease in both the mid‐ and late‐21st century with significant spatial changes. A decrease in the monsoon precipitation is also projected, particularly in the central and southern plains of lower altitudes, which might be highly related to the reduction of wet air from the Indian Ocean and the increment in outflow to the east of the IRB. For winter and spring precipitation, except for the late‐21st century under the representative climate pathway (RCP) 2.6, a decreasing trend is projected, which might be caused by the reduction of water vapour from the west. This will further weaken the availability of water resources in these seasons, especially in the upper IRB of higher altitudes.